Muscle metabolites and performance during high-intensity, intermittent exercise - Hargreaves, M.; McKenna, M.; Jenkins, D. G.; Warmington, S. A.; Li, J.; Snow, R. J.; Febbraio, M. A. (Journal of Applied Physiology, 1998)
Six men were studied during four 30-s ``all-out`` exercise bouts on an air-braked cycle ergometer. The first three exercise bouts were separated by 4 min of passive recovery; after the third bout, subjects rested for 4 min, exercised for 30 min at 30-35% peak O2 consumption, and rested for a further 60 min before completing the fourth exercise bout. Peak power and total work were reduced (P , 0.05) during bout 3 [765 6 60 (SE)W; 15.8 6 1.0 kJ] compared with bout 1 (1,168655W, 23.861.2 kJ), but no difference in exercise performance was observed between bouts 1 and 4 (1,094 6 64 W, 23.2 6 1.4 kJ). Before bout 3, muscle ATP, creatine phosphate (CP), glycogen, pH, and sarcoplasmic reticulum (SR) Ca21 uptake were reduced, while muscle lactate and inosine 58-monophosphate were increased. Muscle ATP and glycogen before bout 4 remained lower than values before bout 1 (P , 0.05), but there were no differences in muscle inosine 58-monophosphate, lactate, pH, and SR Ca21 uptake. Muscle CP levels before bout 4 had increased above resting levels. Consistent with the decline in muscle ATP were increases in hypoxanthine and inosine before bouts 3 and 4. The decline in exercise performance does not appear to be related to a reduction in muscle glycogen. Instead, it may be caused by reduced CP availability, increased H1 concentration, impairment in SR function, or some other fatigue-inducing agent.